Seasonality and antibiotic resistance of Campylobacter in Turkish chicken meat - Ozbey, Gokben; Tasdemir, Bulent (Ist Zooprofilattico Sperimentale Abruzzo & Molise G Caporale-Izs A&M, 2014)
This study investigated the seasonal prevalence and the antimicrobial susceptibility of Campylobacter jejuni and Campylobacter coli in 264 samples of chicken meat. The samples encompassed wings (n=88), breasts (n=79) and thighs (n=97) and were purchased from different butcheries and markets in Elazig province, in Eastern Turkey, between December 2009 and November 2010. The meat samples were tested for Campylobacter presence and the collected isolates were identified as Campylobacter jejuni and Campylobacter coli using polymerase chain reaction (PCR). Resistance rates to 7 antimicrobials were investigated by the disk diffusion method. Campylobacter jejuni was found at a higher prevalence (41.7%) than C. coli (14.4%); C. jejuni was isolated most frequently from breast samples (53.2%) than from thighs (40.2%) and wings (32.9%) samples. The prevalence of C. jejuni and C. coli peaked during the Summer (June-August), with the highest peak occurring in July (77.3%). The lowest prevalence (30%) was detected in February. The prevalence in the Summer (June-August) was significantly higher (71.2%) than the one reported during the Winter (December-February) (39.4%, P < 0.05). The highest resistance rate among C. jejuni isolates was observed to tetracycline (38.2%), nalidixic acid (29.1%), and ciprofloxacin (24.5%). Campylobacter coli also showed a high resistance to these antibiotics, although in slightly different proportions: tetracycline (42.1%), ciprofloxacin (31.6%), and nalidixic acid (26.3%). None of the C. jejuni or C. coli isolates was resistant to gentamicin.
Variazioni stagionali e resistenza ad antibiotici del Campylobacter in campioni di carne di pollame in turchia
Keywords: Antimicrobial resistance; Chicken meat; Campylobacter coli; Campylobacter jejuni; Seasonal prevalence